Sandoz Studies, Volume 1 : Women in the Writings of Mari Sandoz - Smith, Shannon D., 1958-; Laegreid, Renee M.; Project Muse. (Lincoln : University of Nebraska Press, 2019)
Mari Sandoz, born on Mirage Flats, south of Hay Springs, Nebraska, on May 11, 1896, was the eldest daughter of Swiss immigrants. She experienced firsthand the difficulties and pleasures of the family's remote plains existence and early on developed a strong desire to write. Her keen eye for detail combined with meticulous research enabled her to become one of the most valued authorities of her time on the history of the plains and the culture of Native Americans. Women in the Writings of Mari Sandoz is the first volume of the Sandoz Studies series, a collection of thematically grouped essays that feature writing by and about Mari Sandoz and her work. When Sandoz wrote about the women she knew and studied, she did not shy away from drawing attention to the sacrifices, hardships, and disappointments they endured to forge a life in the harsh plains environment. But she also wrote about moments of joy, friendship, and--for some--a connection to the land that encouraged them to carry on. The scholarly essays and writings of Sandoz contained in this book help place her work into broader contexts, enriching our understanding of her as an author and as a woman deeply connected to the Sandhills of Nebraska.
Cover; Title Page; Copyright Page; Contents; List of Illustrations; Foreword; Acknowledgments; Introduction; 1. These Were the Sandhills Women; 2. The Vine; 3. The Gender of Drought in Mari Sandoz's "The Vine"; 4. Excerpt from Slogum House; 5. Mari Sandoz's Slogum House; 6. Excerpt from "What the Sioux Taught Me"; 7. Women in These Were the Sioux; 8. Sandoz Constructing Women with "Well-Knit Bone and Nerve"; Bibliography; List of Contributors; Index
Includes bibliographical references and index.
Description based on print version record.
JSTOR
Keywords: Sandoz, Mari, -- 1896-1966 -- Criticism and interpretation; Sandoz, Mari, -- 1896-1966 -- Criticism and interpretation; Sandoz, Mari, -- 1896-1966; Women in literature; Femmes dans la littérature.; LITERARY CRITICISM / American / General; Women in literature; Criticism, interpretation, etc